Honey: a realistic antimicrobal for disorders of the skin - McLoone, Pauline; Warnock, Mary; Fyfe, Lorna (My University, 2016)
Resistance of pathogenic micro-organisms to antibiotics is a serious global health concern. In this review, research investigating the antimicrobial properties of honeys from around the world, against skin relevant microbes is evaluated. A plethora of in vitro studies have revealed that honeys from all over the world have potent microbicidal activity against dermatologically important microbes. Moreover, in vitro studies have shown that honey can reduce microbial pathogenicity as well as reverse anti-microbial resistance. Studies investigating the antimicrobial properties of honey in vivo have been more controversial. It is evident that innovative research is required to exploit the anti-microbial properties of honey for clinical use and to determine the efficacy of honey in the treatment of a range of skin disorders with a microbiological aetiology
Keywords: Anti-microbial; dermatology; honey; wound infections